Electroacupuncture and Moxibustion-Like Stimulation Relieves Inflammatory Muscle Pain by Activating Local Distinct Layer Somatosensory Afferent Fibers - Chen, Lizhen; Wang, Xiaoyu; Zhang, Xiaoning; Wan, Hongye; Su, Yangshuai; He, Wei; Xie, Yikuan; Jing, Xianghong (Frontiers in Neuroscience, 2021)
Recent studies have shown that both superficial and deep acupuncture produced clinically relevant and persistent effect on chronic pain, and that seraval types of somatic primary afferents played critical roles in acupuncture and moxibustion analgesia. However, there is yet no accepted mechanism by which layer of primary afferents is activated by acupuncture to relieve chronic pain persistently. The aim of this study is to investigate the role of distinct peripheral afferents in different layers of local tissue (muscle or skin) in chronic pain relief driven by acupuncture and moxibustion. Muscular A-fibers activated by deep electroacupuncture (dEA) with lower intensity (approximately 1mA) persistently alleviated muscular inflammatory pain. Meanwhile, cutaneous C-nociceptors excited by noxious moxibustion-like stimulation (MS) and topical application of capsaicin (CAP) on local acupoint area produced durable analgesic effect as well. Additionally, spontaneous activity of C-fibers caused by muscular inflammation was also inhibited by dEA and CAP. Furthermore, decreases in pain induced by dEA disappeared after deep A-fibers were demyelinated by cobra venom, whereas CAP failed to relieve pain following cutaneous denervation. Collectively, these results indicate that dEA and MS ameliorate inflammatory muscle pain through distinct neural pathway in different layers of somatic tissue, the fomer is achieved by activating muscular A-fibers, while the latter is mediated by activating cutaneous C-fibers.